Investigating the difference in Malaysian undergraduates’ academic achievement and learning interest across HyFlex learning modes - Teh, Liang Jing; Wong, Su Luan; Md Khambari, Mas Nida; Abdul Hamed, Ahmad Sarji; Abdul Rani, Mohd Zariat; Sai, Hong Tang (Ieee-inst Electrical Electronics Engineers, 2024)
There is a lack of knowledge on the difference in Malaysian undergraduates’ academic achievement and learning interest between physical (P), online synchronous (OS), and online asynchronous (OA) learning modes in Hybrid-flexible (HyFlex) lab sessions. Together with the inherent challenges of HyFlex learning, there is a need to conduct this study. This multimethod design study was conducted at a public university in Malaysia. The quantitative and qualitative strands of this study involved 65 and eight participants respectively. Multivariate analysis of variance showed no significant difference in students’ academic achievement among the three learning modes whereas a significant difference in their learning interest was found between P and OA learning modes. Thematic analysis indicated that the multiple learning modes, mandatory learning evidence, instructor feedback, and students’ priorities contributed to students’ academic achievement across learning modes. The flexibility in learning also enhanced students’ overall learning interest. The physical presence of peers and instructors and students’ familiarity with P learning also enhanced students’ learning interest in the P mode. On the other hand, the feelings of disconnection and technical issues experienced by the students reduced their interest in learning in the OA mode. This study implies the opportunity for developing countries to expand access to education cost-effectively and enhance future leaders’ digital literacy. Nevertheless, the findings also imply challenges such as time and financial constraints, the existing digital divide, and the potential resistance from traditional educators.